STOCK STRUCTURE OF FLYING FISH (CYPSELURUS POECILOPTERUS) IN THE EASTERN INDONESIA WATER BASED ON MORPHOMETRIC AND MERISTIC VARIATION - Tuapetel, Friesland; Kadarusman, Kadarusman; Syahailatua, Augy; Boli, Paulus; Indrayani, Indrayani; Wujdi, Arief (BAWAL Widya Riset Perikanan Tangkap, 2023)
Flying fish Cypselurus poecilopterus is a small pelagic fish resource that plays an important ecological and economic role. However, information regarding the structure of its stock in East Indonesian waters is still limited. This study aims to identify stock structure based on morphometric, meristic approaches, and associated with environmental factors. Fish samples were taken during one fishing season (June-September) in 2015 and 2021 in the waters of West Papua and East Seram where the Lydakker line passes, using the method of observation and purposive sampling, then the data were analyzed descriptively and t-test. The results of observations on 23 morphometric characters and 5 meristic features showed a significant difference, so it is estimated that flying fish stocks are composed of 2 sub-populations. Differences in morphometric and meristic parameters are affected by different environmental conditions in the two waters. This information is expected to be useful for the management and sustainable use of flying fish resources.